2020
DOI: 10.1088/1757-899x/960/3/032099
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance and Energy Efficiency of Lightweight Steel Buildings: a Case-Study

Abstract: Steel façade systems follow the actual tendencies in construction offering robust and sustainable solutions, able to answer to actual conditions and to offer adequate interior thermal comfort. The modern sandwich panels provided by the current façade system producers combine the required thermal resistance by varying the thermal insulation material and its thickness with the required structural demands. In addition, the façade layer could be over-coated with different materials, thus offering the required arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The thermal bridges formed by the accelerated use of steel have motivated many researchers to put efforts into researching in this field, analyzing thermal performance [150,162], and its improvement [163][164][165] or mitigating thermal bridges [48,166], the importance of flanking thermal losses [17], the importance of the size and shape of steel studs on the thermal performance [1], numerical simulations of CFS framed walls [146] and CFS buildings [153], development of analytical methods [156,158] and in situ measurement methods [161,167] to estimate thermal transmittance, comparisons between different methods [156,166], thermal insulation [18,157,168,169], the interaction of thermal and sound insulation [19], and thermal performance and energy efficiency [170][171][172]. Table 2 summarizes the important research works performed over the last two decades on the thermal performance of CFS structures.…”
Section: Existing Studies On the Thermal Performance Of Cfs Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal bridges formed by the accelerated use of steel have motivated many researchers to put efforts into researching in this field, analyzing thermal performance [150,162], and its improvement [163][164][165] or mitigating thermal bridges [48,166], the importance of flanking thermal losses [17], the importance of the size and shape of steel studs on the thermal performance [1], numerical simulations of CFS framed walls [146] and CFS buildings [153], development of analytical methods [156,158] and in situ measurement methods [161,167] to estimate thermal transmittance, comparisons between different methods [156,166], thermal insulation [18,157,168,169], the interaction of thermal and sound insulation [19], and thermal performance and energy efficiency [170][171][172]. Table 2 summarizes the important research works performed over the last two decades on the thermal performance of CFS structures.…”
Section: Existing Studies On the Thermal Performance Of Cfs Structuresmentioning
confidence: 99%
“…Unlike traditional construction, the thermal performance of CFS buildings is highly dependent on the thermal insulation used in such buildings [16,171]. Roque and Santos [18] showed that the location of thermal insulation in CFS framed facade walls has a huge impact on its thermal performance.…”
Section: Thermal Bridge Mitigation Strategiesmentioning
confidence: 99%
“…Several studies were made to identify the proper materials for the building envelope elements from a holistic design perspective and ease for deconstruction and future reuse of components [26,27]. The chosen thermal insulation is the recycled-PET thermal wadding, fabricated using polyester fibres recycled from post-consumer polyethylene terephthalate (PET) bottles.…”
Section: The Experimental Modulementioning
confidence: 99%
“…The chosen thermal insulation is the recycled-PET thermal wadding, fabricated using polyester fibres recycled from post-consumer polyethylene terephthalate (PET) bottles. This material has a low environmental impact [22,26], high mechanical resistance, and good physical properties [28]. Another reason for this choice was to stimulate the local economy and the recycling and reuse of materials.…”
Section: The Experimental Modulementioning
confidence: 99%
See 1 more Smart Citation